External validation of Tzanakis scoring system in acute appendicitis in a rural hospital - Lattoo, Mohd Riyaz; Mir, Shabir Ahmad; Ganie, Nayeemul Hassan; Rather, Shabir Hussain (International Journal of Research in Medical Sciences, 2019)
Background: Acute appendicitis is one of the most common cause of acute abdomen surgery. Several scoring systems have been adopted by physicians to aid in the diagnosis and decrease the negative appendicectomy rate. Tzanakis scoring system is one such score. Objective of present study was the validation of this scoring system in our population and compare its accuracy with histopathological examination (HPE). Methods: A retrospective study was carried out at the Department of Surgery at Mohammad Afzal Beigh Memorial Hospital Anantnag India. Tzanakis score was calculated in 288 patients who underwent appendicectomy from September 2016-2018 and HPE results were analysed. Results: 276 patients were eligible for the study. The sensitivity and specificity of Tzanakis score in diagnosing appendicitis was 90.66% and 73.68% respectively. The overall diagnostic accuracy was 86.23% with positive predictive value of 97.89% and negative predictive value of 36.84%. Conclusions: Tzanakis scoring system is an accurate modality in establishing the diagnosis of acute appendicitis and preventing a negative laparotomy.